Elucidating interaction mechanisms of protein and diacylglycerol at the interface on the static storage stability of partially crystalline emulsions through a multiscale approach - Xie, Pengkai; Zhang, Zhen; Lee, Yee-Ying; Xie, Rui; Lai, Junqi; Zou, Shuo; Tan, Chin Ping; Zhang, Yufei; Huang, Ying; Xu, Geyang; Wang, Yong (Elsevier B.V., 2025)
Partially crystalline emulsions (PCEs) such as whipping cream and aerated emulsions can be stored in refrigerated or frozen conditions, but maintaining their stability at room temperature for an extended period is a significant challenge. Within the storage range of long shelf life, this study found that enriched diacylglycerol (DAG) oil-based PCEs have the ability to significantly improve the emulsion stability compared to triacylglycerol (TAG)-based PCEs. Subsequently, a multi-scale research approach was adopted, gradually revealing the underlying stability mechanisms. Studies have demonstrated that the interaction between the flexible casein and DAG in milk proteins predominantly happened at the interface of fat globules, heightening the spatial hindrance of the interface membrane to ensure the enduring stability of fat globules during storage. Moreover, the correlation between interfacial rheology and Q-CMD, molecular dynamics simulations has been confirmed from a microscopic and molecular level perspective, validating the mechanisms behind macroscopic performance patterns. Furthermore, Q-CMD and interfacial rheology demonstrated that the active hydroxyl groups of DAG and proteins can exist together to cooperatively control the strength of the interfacial membrane, thus laying the foundation for controlling the partial coalescence behavior of PCEs fat globules. This article elucidated the mechanism by which the interaction between casein and DAG enhances the stability of PCEs, providing a theoretical basis for the design of long shelf life PCEs.